Credibility : how leaders gain and lose it, why people demand it - Kouzes, James M., 1945- (Jossey-Bass, 2011)
"The first true revision of the classic book from the bestselling author of The Leadership Challenge As the world falls deeper into economic downturns and warfare, the question of credibility (how leaders gain and lose it) is more important than ever. Building on their research from The Leadership Challenge, James Kouzes and Barry Posner explore in Credibility why leadership is above all a relationship, with credibility as the cornerstone, and why leaders must "Say what you mean and mean what you say." This first full revision of the book since its initial publication in 1993 features new case studies from around the world, fully updated data and research, and a streamlined format. Written by the premier leadership experts working today, Credibility: Reveals the six key disciplines that strengthen a leader's capacity for developing and sustaining credibility. Provides rich examples of real managers in action Includes updates to?the applications?and research This personal, inspiring, and genuine guide helps you understand the fundamental importance of credibility for building personal and organizational success"--Provided by publisher.